Exploring user engagement with social media in libraries : practices, perceptions and contributing factors - Norsharyna Shafawi
The mainstream use of social media has impacted the library as it has been identified to be an efficient platform for libraries to foster networking and enhance engagement with their user community. The unique characteristics of social media with 'high tech', 'interactive' blend with the 'human touch' give a valuable means for libraries to provide information resources and services beyond their physical walls. However, despite its widespread usage, an engagement rate on social media was still low among library users and evaluation of social media use remain elusive and scarce in the library literature. Prior studies have yet to reveal to what extent the presence of social media triggers users' awareness and influence their engagement. Subsequently, how it further impacts the actual library usage among end-users. Therefore, the study aimed to investigate the factors that drive users' engagement with social media and further examined the relationship of users' engagement with social media and actual library usage. A mixed method approach was employed, and the study population consists of selected State Public and Academic Libraries in Malaysia. The integration of DeLone and McLean's Information Systems Success Model (ISSM), Perceived Interactivity (PI) and Consumer Online Engagement (COE) models were adopted and adapted to establish the direction of the research. A total of 334 respondents which consisted of library users; and 11 interview participants were the professional librarians. The findings indicated that Information Quality, Perceived Interactivity, and Perceived Net Benefit have empirically proven to be significant predictors of users' engagement with social media. The study also revealed that two dimensions of online engagement (affective and behavioural) have a positive and statistically significant effect on actual library use; while cognitive engagement proved to be insignificant. The study was significant in providing libraries a holistic overview about determinants of social media engagement and offers guidelines on the evaluation of library social media application in libraries. It also explored the potential and gauges the prospective areas of improvement for harnessing use of library resources and services in meeting users' ever-changing needs via the power of social media engagement.